Understanding Crime in Islamic Jurisprudence and Muslim Societies (Part 1 of the author’s lecture series ‘Crime in Islamic Legal Tradition: A Reappraisal’) - Hamzić, Vanja (2014)
This lecture discusses some of the elementary concepts relating to Islamic criminal law and justice and then briefly focuses on four specific examples, some historical and some contemporary, of the diversity immanent to this field; a diversity based on what might be termed as a culture of judicial disagreement - a culture of ikhtilaf.